Impact of COVID‐19 stay‐at‐home orders on weight‐related behaviours among patients with obesity. Issue 5 (12th July 2020) - Almandoz, Jaime P.; Xie, Luyu; Schellinger, Jeffrey N.; Mathew, Matthew Sunil; Gazda, Chellse; Ofori, Ashley; Kukreja, Sachin; Messiah, Sarah E.
Summary: How the impact of the COVID‐19 stay‐at‐home orders is influencing physical, mental and financial health among vulnerable populations, including those with obesity is unknown. The aim of the current study was to explore the health implications of COVID‐19 among a sample of adults with obesity. A retrospective medical chart review identified patients with obesity from an obesity medicine clinic and a bariatric surgery (MBS) practice. Patients completed an online survey from April 15, 2020 to May 31, 2020 to assess COVID‐19 status and health behaviours during stay‐at‐home orders. Logistic regression models examined the impact of these orders on anxiety and depression by ethnic group. A total of 123 patients (87% female, mean age 51.2 years [SD 13.0]), mean BMI 40.2 [SD 6.7], 49.2% non‐Hispanic white (NHW), 28.7% non‐Hispanic black, 16.4% Hispanic, 7% other ethnicity and 33.1% completed MBS were included. Two patients tested positive for severe acute respiratory syndrome coronavirus 2 and 14.6% reported symptoms. Then, 72.8% reported increased anxiety and 83.6% increased depression since stay‐at‐home orders were initiated. Also 69.6% reported more difficultly in achieving weight loss goals, less exercise time (47.9%) and intensity (55.8%), increased stockpiling of food (49.6%) and stress eating (61.2%). Hispanics were less likely to report anxiety vs NHWs (adjusted odds ratios 0.16; 95% CI, 0.05‐0.49; P = .009). Results here showed the COVID‐19 pandemic is having a significant impact on patients with obesity regardless of infection status. These results can inform clinicians and healthcare professionals about effective strategies to minimize COVID‐19 negative outcomes for this vulnerable population now and in post‐COVID‐19 recovery efforts.